Study of microstructure, phases and microhardness of metallic coatings deposited by flame thermal spray - Benabbas, Abderrahim (universite de bouira, 2007)
The recharging technique by thermal spraying offers the opportunity of renovating theworn surface parts of a machine element to give it again a new technical life despite its previous degradation in service. This process has consequently interesting economic impacts. In order to improve the adherence between 100Cr6 steel deposits and the substrate material (left worn crankshafts), company SNC ATRA of B´ eja¨ıa uses at present a composite formed by (100Cr6 steel/molybdenum bond coat of 0.2mm thick/crankshaft substrate). As a matter of fact, it is shown in the present work that the molybdenum bond coat is not appropriate since, for the 0.2mm thickness, lateral cracks are observed in the middle of the bond coat. On the other hand, our experiment is that a deposit of 100Cr6 steel projected directly on the substrate seems more promising since no gaps or cracks were detected at the “deposit/substrate” interface of this two-material composite. Lastly, phase analysis using X-ray diffraction confirmed that during spraying process, a stable -phase (bcc) of 100Cr6 wire was transformed to a new phase of -phase (fcc). The coatings exhibited the higher microhardness which would contribute to increase wear resistance.
Keywords: Flame spraying Coating microstructure Bond coat Microhardness tests XRD/EDS